Tarascan pottery production in Michoacán, Mexico : an ethnoarchaeological perspective - Williams, Eduardo (Archaeopress Publishing Ltd, 2017)
This work examines a contemporary pottery tradition in Mesoamerica, but also looks back to the earliest examples of cultural development in this area. By means of ethnographic analogy and ceramic ecology, this study seeks to shed light on a modern indigenous community and on the theory, method and practice of ethnoarchaeology.